The Determinants of Husband Behavior in The Care of Pregnant Women (Department of Public Health, Faculty of Sport Science, Universitas Negeri Semarang, 2016)
Maternal Mortality Rate (MMR) and Infant Mortality Rate (IMR) in Banyumas District are still below The Minimum Service Standard (MSS), especially in Puskesmas (Public Health Center) I Ajibarang. The strategies for reducing maternal mortality are conducted by increasing mother’s health status during pregnancy. This study aims at determining the factors of husband’s role in women’s prenatal care. Cross-sectional method was used. The populations were all of the pregnant women in Puskesmas I Ajibarang. Proportional random sampling was applied to select 90 pregnant women. Logistic regression was used to determine factors. Theory of planned behavior was used to explore the determinants of husband’s role. The results show that the level of education, family income, the knowledge, the attitude, and subjective norm are not related to husband’s role in mother prenatal care. However, husband’s behavior control (p=0.045) and intention (p=0.000) have relation with husband’s role in women prenatal care. Variable of intention is the most dominant variable related to husband’s role in women’s prenatal care.